IMPROVING STUDENTS VOCABULARY MASTERY BY USING QUIZIZZ GAME BASED LEARNING AT JUNIOR HIGH SCHOOL - Pratiwi, Annisa Dwi; Tuna, Jim R.; Samola, Nurmin (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
This study was conducted to determine whether the use of Quizizz game based learning applications can improve students vocabulary mastery or not especially in SMP Negeri 6 Tondano In conducting this research a quantitative method with a pre experimental design was used The subject of this research is one of the classes namely the ninth grade IX at SMP Negeri 6 Tondano totaling 15 students Data collection instruments were pre test before treatment and post test after treatment The tests were in the form of multiple choice and matching tests The results of this study showed that the average scores of the post test is higher 88 33 than the mean scores of the pre test 43 33 Based on the results of the study it was concluded that the use of Quizizz game based learning media was very effective and succeeded in improving students vocabulary especially on the meaning of words and equivalent meaning synonyms and making students more active and class learning more fun < p>